AHA Life's essential 8 and ideal cardiovascular health among young adults - Naman S. Shetty; Vibhu Parcha; Nirav Patel; Ishant Yadav; Chandan Basetty; Cynthia Li; Ambarish Pandey; Rajat Kalra; Peng Li; Garima Arora; Pankaj Arora (Elsevier, 2023)
Objective: This study assessed cardiovascular health (CVH) in young adults using the 2022 AHA Life's Essential 8 (LE8) score and compared it with the Life's Simple 7 (LS7) score. Methods: Individuals aged 18 to 44 years without a history of cardiovascular disease in the National Health and Nutrition Examination Survey (NHANES) cycles were included. Data from 2007-2008 to 2017-2018 were combined to create 3 groups (2007-2010, 2011-2014, and 2015-2018) for analysis. The LE8 score and its components were computed in the overall population and stratified by sex and race/ethnicity. Trends for the LE8 score were analyzed using adjusted linear regression models. Results: Among 12,197 young adults, representing an estimated 89.4 million individuals, from the NHANES 2007-2018, the CVH in the overall population and across all subgroups was stable (Ptrend >0.05). The blood lipid score improved across all subgroups (Ptrend:<0.05). The mean LE8 score was 69.2±0.3. Females (71.4±0.4) had better CVH compared with males (67.2±0.4). Non-Hispanic Black individuals (65.1± 0.3) had the lowest CVH compared with Non-Hispanic White individuals (69.9±0.5), Mexican American individuals (67.3±0.3), and other race individuals (71.2±0.4). Of the 46.1 million individuals categorized as intermediate CVH by the LS7 score, 8.1 million (17.6%) and 2.3 million (5.0%) were reclassified to poor and ideal CVH by the LE8 score, respectively. Of the 40.1 million individuals categorized as ideal CVH by the LS7 score, 18.9 million (47.1%) and 0.1 million (0.2%) were reclassified to poor CVH and intermediate CVH by the LE8 score, respectively. Conclusion: Among US young adults, there has been no improvement in CVH over the last decade with notable sex and race/ethnicity-associated differences in the LE8 score. Nearly 1 in 4 young adults had ideal CVH using the LE8 score compared with 1 in 2 individuals using the LS7 score.